L'Evolution de la mémoire et la notion du temps : leçons au collège de France 1927-1928 - Janet, Pierre (Paris L'Harmattan, 2006)
In 1927-1928, Pierre Janet (1859-1947) gave a famous series of lectures at the Collège de France on the evolution of memory and the notion of time. For Janet, temporal behaviours can be grouped, in terms of their progressive evolution, into three main levels: 1° duration, 2° elementary memory, 3° the organisation of time. No other author has delved so deeply into the structure of time and memory. A work to be discovered and pondered. (Translated with Deepl.com)
Keywords: Psychology; Memory; Time